2022
DOI: 10.3390/vetsci9090499
|View full text |Cite
|
Sign up to set email alerts
|

Redox Status and Hematological Variables in Melatonin-Treated Ewes during Early Pregnancy under Heat Stress

Abstract: The preovulatory follicles and preimplantation stage embryos are found to be rather sensitive to heat stress due to their low potential for scavenging reactive oxygen species (ROS). The aim of the present study was to assess the impact of melatonin administration on redox status and hematological variables during the preovulatory period and early stages of embryogenesis in heat-stressed ewes in vivo. Forty Karagouniko-breed ewes were divided in two groups, the melatonin (M, n = 20) group and control (C, n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In domestic mammals, melatonin has been shown to regulate gene expression required for the synthesis of antioxidants such as GSH‐Px and SOD, and to increase mRNA synthesis (Mayo et al., 2002). It has been reported that reproductive potential can be increased as a result of raised activity of GSH‐Px and SOD enzymes, alone or in combination, in mammalian oocytes and/or embryos (Bouroutzika et al., 2022; Shi et al., 2009; Song et al., 2019; Su et al., 2015; Tamura et al., 2012). It has been reported that melatonin (18 mg) administered 8 days prior to superovulation in prepubertal lambs increases SOD and GSH‐Px activities in cumulus cells, reaching higher concentrations than the control group and causing less ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic mammals, melatonin has been shown to regulate gene expression required for the synthesis of antioxidants such as GSH‐Px and SOD, and to increase mRNA synthesis (Mayo et al., 2002). It has been reported that reproductive potential can be increased as a result of raised activity of GSH‐Px and SOD enzymes, alone or in combination, in mammalian oocytes and/or embryos (Bouroutzika et al., 2022; Shi et al., 2009; Song et al., 2019; Su et al., 2015; Tamura et al., 2012). It has been reported that melatonin (18 mg) administered 8 days prior to superovulation in prepubertal lambs increases SOD and GSH‐Px activities in cumulus cells, reaching higher concentrations than the control group and causing less ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that melatonin has a good antioxidant effect, and is a free radical scavenger and broad-spectrum antioxidant. 15,16 Melatonin can clear free radicals and increase antioxidant enzyme activity. 17,18 Previously studies showed that melatonin upregulated the expression of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of melatonin varies widely in the gastrointestinal tract. Previous studies showed that melatonin has a good antioxidant effect, and is a free radical scavenger and broad‐spectrum antioxidant 15,16 . Melatonin can clear free radicals and increase antioxidant enzyme activity 17,18 .…”
Section: Introductionmentioning
confidence: 99%